Tournaments with Gaps - Lorens Imhof; Matthias Kräkel (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
A standard tournament contract specifies only tournament prizes. If agents' performance is measured on a cardinal scale, the principal can complement the tournament contract by a gap which defines the minimum distance by which the best performing agent must beat the second best to receive the winner prize. We analyze a tournament with two risk averse agents. Under unlimited liability, the principal strictly benefits from a gap by partially insuring the agents and thereby reducing labor costs. If the agents are protected by limited liability, the principal sticks to the standard tournament.
urn:nbn:de:bvb:19-epub-17236-1
Keywords: C72; D86; 330; limited liability; moral hazard; risk aversion; tournament; unlimited liability